Worldwide Advances in Communication Networks
X, 186 p.
Keywords: The symposium on "Worldwide Advances in Communications Networks" which was held on May 14-15, 1992 at GMU was an ambitious attempt to bring together leaders in the communications area to discuss the major issues in this rapidly-changing technology. The symposium was a success and many of the ideas presented at the conference are being implemented. This proceeding contains the majority of the papers presented at the symposium and abstracts of the remainder. The papers may be divided into seven general categories. The first five papers explore some important design issues for high speed networks (gigabit networks). Traffic modelling, quality of service guarantees, switching alternatives, and routing are discussed. The next two papers focus on applications for broadband communications. Weinstein begins by asking, "ARE THERE ANY APPLICATIONS?" and then proceeds to develop a wide variety of potential uses. Personick concentrates on multimedia applications. The next three papers deal with Personal Communications Services (PCS) and the notion of communicating with anyone, at any time, anywhere. Several of the key technical issues such as CDMA vs TDMA are analyzed in detail. The fourth area is satellite communications. Two papers discuss some of the major changes that are taking place and potential new systems. The next two papers discuss signal coding and digital video. Jayant provides an excellent overview of the impressive capabilities that are available for the compression of speech, audio, image, and video signals. Bellisio concentrates on video encoding.